Psychiatric illness and pregnancy: A literature review - Mohsen M.A. Abdelhafez; Karim A.M. Ahmed; Nashwa A.M. Ahmed; Mohd Hamdy Ismail; Mohd Nazri Mohd Daud; Nicholas Pang Tze Ping; AyaM. Eldiasty; Mohd Fariz Amri; Mohammad Saffree Jeffree; Fairrul Kadir; Dg Marshitah Pg Baharuddin; Mohammed Firdaus Bolong; et al. (Elsevier Ltd, 2023)
Background Women of reproductive age frequently suffer from psychiatric disorders. The risk of developing anxiety, bipolar, and depressive disorders is especially significant during the perinatal period. Objectives This article aims to identify and discuss the different psychiatric conditions that might affect pregnant women and update the mother's carers about the recent and updated bidirectional relationship between psychiatric disease and adverse pregnancy outcomes, As well as the most updates in diagnostic and management strategies. Methods A thorough analysis of the literature was conducted using database searches in EMBASE, Science Direct, Google Scholar, Scopus, and PubMed to obtain the objectives and aim of the study. Results The presence of maternal mental illness during pregnancy has been linked to preterm delivery, newborn hypoglycemia, poor neurodevelopmental outcomes, and disturbed attachment. Placental anomalies, small-for-gestational-age foetuses, foetal discomfort, and stillbirth are among more undesirable perinatal outcomes. Conclusions Pregnancy-related psychiatric disorders are frequent. The outcomes for pregnant women, infants, and women's health are all improved by proper diagnosis and treatment of psychiatric problems.